Remembering, Reflecting, Reframing: Examining Students’ Long-Term Perceptions of an Innovative Model for University Teaching - Ritella, Giuseppe; Di Maso, Rosa; McLay, Katherine; Annese, Susanna; Ligorio, Maria Beatrice (Frontiers in Psychology, 2020)
This article presents a follow-up examination of 10 iterations of a blended course on educational psychology and e-learning carried out at the University of Bari. All iterations of the course considered in this study were designed using the Constructive and Collaborative Participation (CCP) model. Our main research questions are: What are the students’ long lasting memories of this course? How do the students use the skills and the competences acquired through the course across an extended period of time? In line with these research questions, the aims of this investigation can be summarized as follows: i) to understand the students’ perceptions and long lasting memories of the course and (ii) to investigate the transfer of skills and knowledge across an extended period of time, based on a self-reported survey. The analysis was carried out by administering the survey to all 196 students who took part in the course in the 2005-2015 decade. 96 participants responded to the survey. The survey is designed to collect data in two areas. First, the memories related to the course and second, the way skills and content knowledge acquired during the course have been transferred to and used in other contexts after the course ended. The data were analyzed using a mixed methods approach, which revealed trends in the responses across the decade. In general, participants remembered the teaching methodology and often recalled specific activities such as Role Taking and the creation of products through group-work. These activities and approaches seemed to provide significant learning opportunities for the students. Several students also recalled key concepts and content knowledge acquired during the course. In relation to transfer of skills, participants tended to reuse mostly transversal skills, such as communicative and organizational skills, especially in work contexts. Further, about half of the respondents reused the content knowledge of the course. This analysis is valuable because it allows us to understand the aspects of the model that are significant for the students in the long term, and to discover and interrogate the acquisition and transfer of skills useful for the students’ personal and professional lives beyond the academy.